2013
DOI: 10.3389/fnagi.2013.00067
|View full text |Cite
|
Sign up to set email alerts
|

Adult age-dependent differences in resting-state connectivity within and between visual-attention and sensorimotor networks

Abstract: Healthy aging is accompanied by structural and functional changes in the brain, among which a loss of neural specificity (i.e., dedifferentiation) is one of the most consistent findings. Little is known, however, about changes in interregional integration underlying a dedifferentiation across different functional systems. In a large sample (n = 399) of healthy adults aged from 18 to 85 years, we analyzed age-dependent differences in resting-state (RS) (task-independent) functional connectivity (FC) of a set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 78 publications
3
39
0
Order By: Relevance
“…We observed that age was associated with mixed higher and lower weight across the brain, though frontal connections were relatively unaltered. This possibly reflects brain-wide reorganization in age (Grady et al, 2006; Roski et al, 2013) and may explain the higher diversity seen in the DMN with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that age was associated with mixed higher and lower weight across the brain, though frontal connections were relatively unaltered. This possibly reflects brain-wide reorganization in age (Grady et al, 2006; Roski et al, 2013) and may explain the higher diversity seen in the DMN with age.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that aging is associate with dedifferentiation in the brain network, causing brain regions to become less specialized (Li and Lindenberger, 1999; Roski et al, 2013). We observed that age was correlated with higher global graph entropy, particularly strong in the DMN.…”
Section: Discussionmentioning
confidence: 99%
“…Previous imaging studies suggest that aging is related in a complicated way to cerebral functional connectivities, with different brain areas increasing and decreasing with age in connectivity to regions of interest (Bernard et al, 2013; Campbell et al, 2013; Hafkemeijer et al, 2013; Hoffstaedter et al, 2014; Liu et al, 2012; Roski et al, 2013; Taniwaki et al, 2007; Ystad et al, 2010; see also Ferreira and Busatto, 2013 for a review). Here, we observed that age is associated with increased BNM connectivity to subcortical structures including the midbrain and pallidum and decreased connectivity to somatomotor and visual cortices.…”
Section: Discussionmentioning
confidence: 99%
“…The observed age-dependent reductions in anti-correlation between these regions and several of our task-related network nodes might thus reflect difficulties in recruiting task-relevant regions selectively in advanced age, leading to “intrusions” or interference from task-irrelevant cognition (cf. Mason et al, 2007; Roski et al, 2013a; Weissman et al, 2006). Such potentially dysfunctional age-related changes in FC between functionally distinct brain networks (i.e., neural de-differentiation) have been recently reported for visual-attention and sensorimotor networks (Roski et al, 2013b) and might contribute to the behavioural deficits observed in Experiment 1 by undermining proper task-set implementation in the elderly.…”
Section: Methodsmentioning
confidence: 99%